An exploration of the relationship between exposure to violent video games and moral reasoning about violence - Tan, Ee Ee (2021)
The overarching aim of this thesis was to explore the relationships between violent video games (VVGs), moral reasoning about violence, empathy and aggression. This was achieved through a systematic review, psychometric critique, empirical study and a single case study. A systematic review of the association between violent video games exposure (VVGE) and moral development suggested a knowledge gap in the relationship between VVGs and moral reasoning. It also highlighted potential difficulties in measuring moral reasoning as a global construct. Hence, a more specific aspect of moral reasoning was examined in this thesis-moral reasoning about justified and unjustified violence. Acritique of the Moral Interpretations of Interpersonal Violence (MIIV) was conducted to review its suitability as a measure of moral reasoning about violence. Results of the systematic review and psychometric critique informed the design of the empirical studywhich found that VVGE was positively associated with perceptions of justified violence as being acceptable in males. VVGE also predicted moral reasoning about justified violence in males, even after controlling for empathy, childhood exposure to and experience of violence. There was no evidence that moral reasoning about violence mediated the relationship between VVGE and aggression As the empirical study focused on a non-offending sample using a quantitative design, a qualitative approach was taken to explore the relationships between the variables of interest in a female offender with a violent offence. Findings from the four pieces of work culminated in a proposed integrated model reflecting the associations between media violence, moral reasoning, empathy and aggression/offending.